2018
DOI: 10.7554/elife.38281
|View full text |Cite
|
Sign up to set email alerts
|

Range, routing and kinetics of rod signaling in primate retina

Abstract: Stimulus- or context-dependent routing of neural signals through parallel pathways can permit flexible processing of diverse inputs. For example, work in mouse shows that rod photoreceptor signals are routed through several retinal pathways, each specialized for different light levels. This light-level-dependent routing of rod signals has been invoked to explain several human perceptual results, but it has not been tested in primate retina. Here, we show, surprisingly, that rod signals traverse the primate ret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 67 publications
(116 reference statements)
3
69
1
Order By: Relevance
“…Notably, in macaque, direct rod-to-Off-CBC input occurs less frequently than in mouse, a result that may explain the lower contribution of the tertiary rod pathway to scotopic signaling in primates (Grimes et al, 2018a).…”
Section: The Primary Rod Pathway Utilizes Specific Off-cbc Circuitsmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, in macaque, direct rod-to-Off-CBC input occurs less frequently than in mouse, a result that may explain the lower contribution of the tertiary rod pathway to scotopic signaling in primates (Grimes et al, 2018a).…”
Section: The Primary Rod Pathway Utilizes Specific Off-cbc Circuitsmentioning
confidence: 96%
“…A recent study showed that primates differ from other species in that rod signals are routed principally through the primary rod pathway, via AII-ACs, even at mesopic light levels (Grimes et al, 2018a). However, it is not known whether all of the five primate Off-CBC types (Boycott and Wässle, 1991;Haverkamp et al, 2003;Puthussery et al, 2013Puthussery et al, , 2014Peng et al, 2019) receive AII -AC input, and thus participate in primary rod pathway signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the assumption is that the rod bipolar pathway dominates at low mesopic light levels and the (assumed faster) rodcone pathway, mediated by gap junctions between rods and cones, contributes substantially at high mesopic light levels (Figure 2). Our recent work (Grimes et al, 2018a) suggests that this is not the case, and that instead rod signals traverse the primate retina primarily through the rod bipolar pathway across light levels.…”
Section: Dynamic Temporal Delaysmentioning
confidence: 96%
“…First, many rod-cone interactions likely involve both retinal and cortical circuits, and isolating the contributions of each circuit can be difficult (Grimes et al, 2015). Second, it is difficult to generalize between rod-cone interactions in primates and rodents due to differences in visually-guided behavior, in the architecture and cellular composition of retinal circuits, and in the routing of signals through those circuits (Grimes, Baudin, Azevedo, & Rieke, 2018a).…”
Section: Linking the Mechanisms Controlling Parallel Neural Processinmentioning
confidence: 99%
“…Three GC types in the mouse retina receive input from the RB pathway at or near visual threshold: the ON α GC and the OFF α and δ GCs, which exhibit high sensitivity to spatial contrast in the visual scene—similar to primate parasol cells —and project to the geniculo-cortical pathway (Ala-Laurila et al, 2011; Ala-Laurila and Rieke, 2014; Dunn et al, 2006; Grimes et al, 2018a; Grimes et al, 2015; Grimes et al, 2014b; Grimes et al, 2018b; Ke et al, 2014; Kuo et al, 2016; Murphy and Rieke, 2006, 2008). Input from the RB pathway to ON α GCs provides the signal that guides behavior at visual threshold (Smeds et al, 2019).…”
Section: Introductionmentioning
confidence: 99%